2015
DOI: 10.3892/mmr.2015.3635
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic dysregulation of endometriosis susceptibility genes (Review)

Abstract: The aim of the present review was to illustrate how dysregulation of hormonal signaling regulates expressional changes of spatially associated genes in endometriosis. From a multi‑platform endometriosis dataset, an integrated analysis was performed of epigenomic changes of several biologically relevant genes that have been validated in the literature. Estrogen receptor (ER) may act as a direct epigenetic driver for endometriosis establishment, maintenance and progression. A majority of endometriosis susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…An enhanced ERβ (ESR2) activity stimulates the progression of endometriosis by inhibiting tumor necrosis factor-α (TNF-α)-induced apoptosis and increasing IL-1β-dependent cellular adhesion and proliferation (101). The steroid hormone-mediated decidualization signaling pathway is considered to be dysregulated in endometriosis (100). Progesterone resistance is associated with endometriosis and contributes to impaired decidualization.…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%
“…An enhanced ERβ (ESR2) activity stimulates the progression of endometriosis by inhibiting tumor necrosis factor-α (TNF-α)-induced apoptosis and increasing IL-1β-dependent cellular adhesion and proliferation (101). The steroid hormone-mediated decidualization signaling pathway is considered to be dysregulated in endometriosis (100). Progesterone resistance is associated with endometriosis and contributes to impaired decidualization.…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%
“…22 The cells of patients with endometriosis are found to have postconception genetic changes in DNA and messenger RNA (mRNA) alterations. 23 It is suggested that sex hormonebinding globulin (SHBG) may transport some contaminant xenoestrogens into the plasma and modulate their bioavailability to cell tissues. 24 What is not commonly considered is that the estrogenic potential of the xenoestrogens and their metabolites can be just as potent as 17β-estradiol.…”
Section: Previous Alternative Therapy Regimensmentioning
confidence: 99%
“…In females, several reproductive diseases have also been associated with epigenetic abnormalities. The occurrence of endometriosis has been linked to the epigenetic deregulation of “endometriosis susceptibility” genes [ 46 48 ]. Women exposed in utero to diethylstilbesterol develop cervical malformations.…”
Section: Epigenetic Changes Associated With Reproductive Diseasementioning
confidence: 99%